Number 41 (November 2000) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2000)
(November 2000) - Ichthyofauna and biogeography of Russell Fork (Big Sandy River - Ohio River). By Steven L. Powers and Patrick A. Ceas Minutes, Business Meeting, 25th Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: ichthyofauna; russell fork; big sandy river